Falsehoods and Bacts about the Jews - "Rathbone, Eleanor F." (London, 1944)
This book is an attempt to highlight the fascinating saga of Jewish groups in India, spread out in Cochin, Bombay and Calcutta- their achievements ans aspirations, their triumphs and travails all as part of India's rich heritage and history.
Keywords: Religion